Salinity Is a Key Determinant for the Microeukaryotic Community in Lake Ecosystems of the Inner Mongolia Plateau, China - Liu, Changqing; Wu, Fan; Jiang, Xingyu; Hu, Yang; Shao, Keqiang; Tang, Xiangming; Qin, Boqiang; Gao, Guang (Frontiers in Microbiology, 2022)
The arid and semiarid areas experienced remarkable lake shrinkage during recent decades due to intensive human activities and climate change, which would result in unprecedented changes of microeukaryotic communities. However, little is known about how climate change affects the structure and ecological mechanisms of microeukaryotic communities in this area. Here, we used an 18S rRNA gene-based high-throughput sequencing approach to explore the structure, interspecies interaction, and assembly processes of the microeukaryotic community in lake ecosystems of the Inner Mongolia Plateau. As a direct result of climate change, salinity has become the key determinant of the lacustrine microeukaryotic community in this region. The microeukaryotic community in this ecosystem can be divided into three groups: salt (Lake Daihai), brackish (Lake Dalinuoer) and freshwater lakes. Co-occurrence network analysis revealed that salinity shapes the interspecies interactions of the microeukaryotic community. This causes interspecies interactions to change from antagonistic to cooperative with an increase in salinity. Phylogenetic-based β-nearest taxon distance analyses revealed that stochastic processes mainly dominated the microeukaryotic community assembly in lake ecosystems of the Inner Mongolia Plateau, and salinity stress drove the assembly processes of the microeukaryotic community from stochastic to deterministic. Overall, these findings expand the current understanding of interspecies interactions and assembly processes of microeukaryotic communities during climate change in lake ecosystems of the Inner Mongolia Plateau.